THE IMPLEMENTATION OF PROJECT-BASED LEARNING TO TEACH SPEAKING A SPOKEN ADVERTISEMENT FOR THE EIGHTH GRADERS OF SMPN 40 SURABAYA - RIFNA HUMAIROH, ANANDA (RETAIN : Journal of Research in English Language Teaching, 2014)
THE IMPLEMENTATION OF PROJECT-BASED LEARNING TO TEACH SPEAKING A SPOKEN ADVERTISEMENT FOR THE EIGHTH GRADERS OF SMPN 40 SURABAYA Ananda Rifna Humairoh English Education Department, Language and Arts Faculty, Surabaya State University. Email: ananda.unesa@gmail.com Dr. Oikurema Purwati, M.Appl English Education Department, Language and Arts Faculty, Surabaya State University. Abstrak BahasaInggrismerupakansalahsatubahasa yang digunakan di duniainternasional.Subjekinijugamenjadipelajaran yang diujikansebagaibahanUjianNasional.Penelitianiniberfokuspadametodepembelajaran yang dapatditerapkandalampengajaranbahasaInggris. DalammengajarbahasaInggris, adaempatketerampilan yang harusdikuasaiolehpesertadidik, yaituMendengarkan, Berbicara, Membaca, danMenulis.Dalamstudiini, keterampilanberbicaramenjaditopikutamapenelitian.Tujuandaripenelitianiniadalahuntukmendeskripsikanpelaksanaanmetode Project-Based Learning dalampengajaran short functional text.MenurutNunan (1989)kemampuanberbicaraterdiridariduajenisucapanatauungkapan, yakniucapaninteraksionaldantransaksional.Siswaharusmenyadarisetiapfungsidanmenggunakannyadenganbenar.Dalammengajarteksfungsionalpendek, adabeberapafiturdaribahasa yang biasanyadigunakandalamteks.Penelitianinibertujuanuntukmendeskripsikanpelaksanaan Project -Based Learning yang diterapkanuntukmengajarkanteksfungsionalpendek, terutamaiklan. Para siswaakandiperkenalkandenganbeberapafiturdariteksfungsionalpendekdenganmelakukanmetodepembelajaran. Penelitianinimerupakanpenelitiankualitatif yang telahdispesikasikansebagaipenelitiandeskriptifkualitatif.Subjekpenelitianiniadalahsiswakelas VIII SMP di SMPN 40 Surabaya.Hasilpenelitianmenunjukkanbahwaadatanggapanpositifterhadappelaksanaan Project-Based Learning.Para siswatampaknyamemilikimotivasidankepercayaandiriuntukberbicarabahasaInggrisdanmengeksplorasikreativitasmerekadalamsesiberbicara.Dengandemikian, PembelajaranBerbasisProyeksebagaiteknikpengajarandianjurkandalammengajariklan di kelas Kata Kunci: KemampuanBerbicara, Project-Based Learning, Iklan Abstract English is one of language which is used in international world. This subject also becomes the lesson which is tested as the examination material. The study focuses on the learning method that can be applied in teaching English. In teaching English, there are four skills that should be mastered by the learner, they are Listening, Speaking, Reading, and Writing. In this study, speaking skill has been the main topic of research. The aim of this research is to describe the implementation of Project-Based Learning in teaching speaking a spoken advertisement. According to Nunan (1989) speaking competence covered with two type of utterances, that are interactional and transactional utterance. The student must aware of each function and use it properly. In teaching short functional text, there are several features of language which typically used in the text. This study has a purpose to describe the implementation of Project-Based Learning that applied to teach short functional text, especially advertisement. The students will be introduced with some features of short functional text by conducting the learning method. This study is a qualitative research which has been specified as descriptive qualitative research. The subject of this research is the eighth graders of Junior High School in SMPN 40 Surabaya. The result of the study showed that there were positive responses toward the implementation of Project-Based Learning. The students seem to have motivation and confidence to speak English and explore their creativity in speaking session. Thus, Project-Based Learning as a teaching method is recommended in teaching a spoken advertisement. Keywords: Speaking skill, Project-Based Learning, Advertisement INTRODUCTION English has been taught at the elementary level to high school and included as one of the subjects tested in the national examination. By learning English, students will be assisted in dealing with the development of the global era and the rapid modernization because English plays an important role. Therefore, it is very important for students to master English as well as other subjects. In learning English, there are four English language skills that must be mastered by the students in the school, namely: hearing skills (Listening), speaking skills (Speaking), reading skills (Reading) and writing skills (Writing). These skills can not be separated and should be taught on an ongoing basis in the teaching-learning process of English subjects. Speaking is one of the important skills to be learned by the students. The mastery of speaking skill is a priority for students and they often evaluate their success in language learning as well as the effectiveness their English learning especially in their spoken language proficiency (Richards, 2008: 19) In this case, in learning speaking English at class there are several factors that affect the educational process. Such factors include teachers, students, the environment, as well as the facilities and systems that are used in the teaching learning process. These factors are related to each other in determining the success of an education because each factor has its own role in the education system. If one factor is not suitable there will be a disruption in the educational process, and it may affect the success of students in learning activities. Commonly, the use of varied instructional model in the learning process in the classroom is still rare and the teachers tend to use conventional models in every learning process. This may be due to the teachers’ lack of learning model mastery. Actually, the mastery of learning models is necessary to improve the professional skills of teachers and encourage students’ motivation in learning process. Most of the learning model used is conventional, whereas in conventional learning the students typically become a passive learner. In this case, the current weakness of model learning in teaching short functional text frequently happened in teaching and learning process nowadays. Mostly, teachers exemplify a short functional text through visual aids, for instance by using the text of advertisement. Consequently, the students are eagerly not being interested to learn more about short functional text. According to that background of study, one of the learning models that are suitable to teach speaking skill is Project-Based Learning. It is stated in the theory from Larmer and Mergendoller, a classroom filled with the students’ project may suggest that students have been engaged in meaningful learning. It is because the project is a series of tasks for the students to learn the content of material in depth comprehension in a group or individually. Project-Based Learning is a learning model that provides an opportunity for students to actively participate in making a project within the group or individual work to improve English language skills, especially in speaking skills (ability to speak). It can be seen from the uniqueness of presentation and exhibition where the learners possibly discuss issue based on PBL principles (Thomas, 2000). Through this learning model, the researcher expects to know students’ speaking and observes whether students feel comfortable and happy to express their opinions and their ideas to be delivered orally through the implementation of this learning method. Project-Based learning refers to students designing, planning, and carrying out an extended project that produces a publicly-exhibited output such as a product, publication, or presentation (Patton: 2012, 13). In this study, students will be instructed to make a project. This project contains the message of short functional text (advertisement). By holding this project, students are going to inquire the basis learning and define the feature of project. In process of making project, it gives students a better understanding about the structure of short functional text especially advertisement. In result, this method also builds students motivation to learn short functional text without any boredom. The similar study has been already conducted by students of State University of Surabaya from class of 2009, who entitled her thesis “The Use of Project–Based Task to Improve Eleventh Graders’ Ability in Writing Hortatory Exposition Text at SMAN 1 NgadirojoPacitan”. The previous study has been applied the same method which support the study, that is Project-Based Learning. However, she provides students with complex tasks based on challenging questions or problems that involve the students’ problem solving. Therefore, the method that is used make students experienced to do the task based on their investigation toward the problems to reflect it into their result of writing perfectly. By looking at the background above, the issues are compelled by the researcher to examine the problem by taking the title "The implementation of Project-Based Learning to Teach Speaking a Spoken Advertisement for the Eighth Graders of SMPN 40 Surabaya”. Based on the background described above, it can be identified the following issues: 1. How is the implementation of Project - Based Learning to teach Speaking Skills of the eighth grade students in SMPN 40 Surabaya? 2. How is the students’ ability in speaking a spoken advertisement during the implementation of Project-Based Learning during the speaking activity in the eighth graders of SMPN 40 Surabaya? 3. How are the students’ responses towards Project-Based Learning during the speaking activity in the eighth graders of SMPN 40 Surabaya? METHOD At the time of the study, the researcher gave the Project-Based Learning methods to provide a new alternative for teaching English, mainly to teach speaking skill. In this study, the researcher acted as the observer in the classroom. Meanwhile, the teacher will teach on the subject of "Advertisement". The researchers will observe the use of Project-Based Learning as a method to teach students’ speaking ability in order to motivate students to be active participants in learning activities, especially in speaking ability. The following data has been summarized based on the research. In this chapter, there are some elements that are used to conduct research, which consists of research design, research subjects, research instruments, data collection techniques, and data analysis techniques. The design of this study is descriptive qualitative research. According to Marshall and Rossman (1999), qualitative research is a research that should provide clear explanation through intuition, complex reasoning, possible research question and conceptual framework, alternative design, and strategies for gathering the data. In this research, the researcher considers all elements during the research held. As it is should be reported in detail written work to represent how the research has been conducted. In qualitative research, the researcher generally uses dominant written conclusion to complete the report of study based on the whole process of data collection technique and data analysis. In addition, the researcher adopted a qualitative descriptive research in this time. This is because the possibility of the implementation process in depth understanding of the current study. As Cohen et al (2007) stated that "qualitative data analysis involves organizing and accounting to explain the data, by defining a learning situation and noting patterns, themes, categories and regularities in the data collection process of the study". According to Ary et al (2010) stated that a qualitative descriptive research is the research which permit the researcher to observe characteristics of some individuals to measure their attitude and opinion towards some issue. For instance, in the field of education the researcher gathers information from the model of learning which applied by a certain teacher to build successful language learning in the class. In accordance with the statement, qualitative descriptive study aimed to clarify the existing variable or the result of English teaching and learning process which is carried out in the classroom. Most of this research is designed to identify English language learning process and described through the words without the counted system. Researcher usually retrieves data through observation and student project results (in the form of advertisement). In this case, the researcher looked at the situation and condition of the class and the student’s ability to obtain research data. Moreover, their speaking ability will be seen from the students speaking result. In this study, the researcher took the study sites in SMPN 40 Surabaya that is locatedat Bangkinganstreet VIII/8 Surabaya. The place of research is chosen because the school still uses the curriculum of 2006 (KTSP) which appropriate with the curriculum in this researchThe implementation of research will took place on 13-27th November 2013. There will be three meetings and each meeting will be observed by the researcher. The subjects in this study were students of class VIII C of SMP 40 Surabaya. The number of students who have received the application of learning models Problem-Based Learning (making advertisement) is 38 students. The subject of the research is chosen because the eight grade students have adequate ability and comprehension to receive the material of short functional text based on the curriculum of 2006. In this study, the researcher will use some instruments to support the qualitative data, namely field note, observation sheet, students’ speaking transcription, and interview. These following instruments would be explained as follows. Field note is a kind of instrument which is usually used in qualitative research. This type of instrument is like a transcribed note that describes all of data collection during observation. The data collection contains the idea thought, activity, question, etc. Actually, in writing field note, the observer should describe the event in the observation as soon as possible. The details of event in the observation are the content of field note. It is generally used to record the data based on the reality in the field. There are two part of field note, that are descriptive and reflective (Santyarini and Susanto, 2014). In the observation, the researcher directly makes a note on the paper to record all the activities in the class. The field note contains the students and teacher’s activity in detailed information. The content of field note will describe the whole process of teaching and learning process, including the activity in the beginning until the end of teaching and learning activity. The activity which is recorded in the field note, such as: greeting, opening the lesson, explaining, discussing, questioning, presenting, closing, etc. All of the activity should be written in detail to depict the entire of teaching and learning process. Observation sheet is one of instruments that usually used in qualitative research to record the data. According to Clerck et al (2011), writing observation sheet involves detailed and concrete observation. It means the observation sheet showed what happened actually in the classroom. It will conclude objective observation made by the researcher which has been gained from the information acquired through conversation among the subject of research. Besides, it also include the general information of teacher and students’ activity in the class. In this observation, pencil and pen are helpful to record their observation. At home, the researcher should transform their short-hand note into detailed description on the computer as quick as possible. Finally, the observation sheet will be used by the researcher as the one of sources to analyze the data of the study. Davidson (2009) stated the transcription is the recording of the speech which its shaped has been transcribed into exploration of written form. In connection with research, this educational research aims to provide an instrument to depict the students’ speaking result in the reflexive document that is written as clear as possible named transcription of speech. It will illustrate enough detailed information from students’ ability, especially speaking ability. This kind of instrument allows more exploration to analyze the data of the study that can be described from the feature of speaking performance in the classroom. A qualitative research concerns with the use of interview. Based on the statement from Brenner (2006) stated that interview is a kind of instruments which intend to obtain information from the informants in oral form based on their own term and meaning towards their own lives, experiences, and cognitive process. In other words, it is designed to give the informants chance to express meaning in their own words as the verbal data for the researcher. Since the researcher and the informant are engaged in ongoing process, the interview is called the interactional relationship. In constructing the interview of study, it should involve some numerous decisions, that are beginning with the structure of interview, the type of questions, the range of topics, and the techniques for obtaining the depth of response that is available during interviewing process. The difference between field note and observation is the field note draws more detailed information than the observation sheet. Here they are the interview questions, there are seven questions in interview session, such as: 1) What do you think about speaking activity in the class? 2) How do you think about this kind of learning method? 3) What do you think about the method that applied by the teacher? Does it motivate you to learn English? 4) What difficulties have you found in speaking class? 5) What is the most interesting section in learning English with Project Based learning? 6) What is the positive impact that you feel from the implementation of Project-Based learning? 7) Do you think that PBL help you to speak up in the class? Do you like the way of teaching method? The researcher will conduct the interview with these seven questions to know how the students’ responses towards Project-Based Learning during the speaking activity in the eighth graders of SMPN 40 Surabaya. Those seven questions will lead them to express their opinion and feeling about the implementation of Project-Based Learning that will be experienced. Besides, the researcher prepares the questions to know the students’ interest and the most interesting part in Project-Based Learning. The interview is also held to know how this method becomes successful in encouraging the students’ willingness of studying English. In this study, the researcher have set up a schedule for achieving the purpose research, namely on 13 up to 27 of November 2013. Approximately it will take for about three weeks in preparation for collection of data of the study, in which there are three meetings each week. According to the plan, in the first meeting, the teacher will explain in detail of advertisement materials so that students can learn more about the material. At this meeting, the researcher starts to observe the subject of study. For the second and the third meeting, the teacher gathered data from the student project and speaking activity in class and the researcher collect the interviews so that the data are the form of teaching and learning process and the students’ speaking result. Moreover, another data that will be obtained by the observer are in the form of students’ opinion and feeling. In addition, there are several considerations to collect data. The researcher should rationally choose a particular instrument. Appropriate instrument in research design is important for the data collection. Actually, the instrument must be related to the type of research. In this study, the researcher also used field notes to obtain the learning process and the student performance during the observation. When the observation is made, the recorded field (field note) containing various notes written by the researcher to gain all of information about the learning process during and after the learning activity. The result of field note will be a written form which divided into descriptive note (describing the general information) and the reflective note (describing the detailed information and personal comments from the observer). Meanwhile, the result of observation sheet will be particularly described the points of teaching and learning process in the classroom that have done by both the teacher and the students. This was done to get a deeper understanding of the study subjects and to write an outline of what the phenomenon at the time. In addition, the researcher must organize teaching and learning design. The researcher not only makes a research but also prepares design of teaching to retrieve student ability, especially preparing the rubric of speaking ability for the students. In this study, the data that is obtained by the researcher is a kind of project (such as advertisement) and student participation (students’ spoken transcription) that is their speaking ability. Researcher can describe the ability of students, especially from their words production through their quality and quantity of the spoken language during the learning process. Other instruments are applied to support this descriptive qualitative study was a interview. Researcher will use the interview to determine students’ response towards the application of the Project-Based Learning. After collecting all the data, the researcher will analyze the data qualitatively. It is described briefly as follows: 1. This study identifies the data obtained from the observation sheet, field notes, the project (advertisement), the participation of the students’ speaking (students’ spoken language) and interview. 2. Data from field notes and observation sheet will be defined and explained descriptively by the researcher in the classroom after the teaching and learning activities. The field note and observation sheet will be analyzed to describe the implementation of Project-Based Learning in Class VIII C 3. The researcher analyzed the results of student projects (such as advertisement) and spoken language (students’ spoken transcription) during the learning process implemented. Before analyzing the results of students’ speaking abilities, researcher should pay attention to some aspects that are important in the content conversational skills generally, such as content, vocabulary, fluency, pronunciation, and grammar. The students’ speaking transcription would be analyzed to describe the students’ ability through their speaking result. The researcher will write descriptively the whole components of speaking that the learner achieved in chapter 4. 4. The data obtained from the interview will be analyzed by a variety of students who expressed their opinions and feeling on the implementation of the Learning Project-Based Learning. This interview will be examined the response of the students toward the implementation of Project-Based Learning. The researcher will describe the result of interview questions by analyzing each questions and answers and stating them generally. 5. Researcher interprets the results of a qualitative analysis based on the nature of classroom descriptive qualitative research design. 6. Finally, researcher makes inferences about teaching learning process as the objective of research to describe the teaching spoken advertisement to the students of class VIII of SMP 40 Surabaya using the Project-Based Learning. RESULT AND DISCUSSION Firstly, to answer the first research question, the researcher considered that it was essential to observe the teaching and learning process done by the teacher. The research was conducted to know the implementation of Project-Based Learning and students’ response towards the application of Project-Based Learning to their speaking ability in producing a spoken advertisement. The data that was analyzed was obtained from the observation sheet and field note which were accomplished three times. Meanwhile, to answer the secondresearch question, the researcher completed the data from students’ transcription and interview. Responding to the last research question, the research should concern about the students’ response by knowing how great their excitement and interest in speaking activity during the implementation of Project-Based Learning. In the second meeting, the students had to submit their advertisement and present it orally in front of the class while the observer analyzed the students’ result of speaking by regarding the components of speaking composition, that were content, fluency, vocabulary, pronunciation, and grammar (structure). The Implementation of Project-Based Learning to Teach Speaking a Spoken Advertisement for the Eighth Graders of SMPN 40 Surabaya The first meeting was conducted in November 13th, 2013. In the opening session, the teacher greeted the students and checked the attendance list whether all of students were present or not. The teacher did not directly teach the students with lots of lesson, but she began the lesson by interacting with them in conversation. After the teacher felt that the students were ready to accept the material, she continued to introduce the topic of lesson, which was short functional text especially the advertisement. Then, the teacher asked the students’ knowledge about the advertisement and its examples to stimulate their prior knowledge. By observing the students’ participation, the researcher knew that the students seemed to find difficulties in selecting the vocabulary for the meaning of advertisement and feel afraid of making an answer in English word. According to this problem, the teacher had provided another stimulus to attract the students’ enthusiasm by asking about the examples of advertisement around them. By keeping this question to students, they started to think about advertisements which exist in their environment. Then, the teacher gave short explanation about type of advertisement. For instance, the teacher encouraged the students to mention many kinds of advertisements in their life. The advertisements were always published everywhere even easily found around the people lives so that the students were asked to mention the existing advertisement which was displayed in their environment. For example, the advertisements in television or the billboard along the roads and public place which were frequently seen by them. In result, they were very active to convey a lot of kinds of advertisements, it might be in the forms of product or service. More than a half from the total of students raised their hands and wanted to answer this question. After conducting the questioning session, the teacher gave some display of advertisements to the students. Several examples of advertisements which had been shared to all of the students would be learned by them with their teacher’s guidance. From the examples given, the students examined what the appropriate components or points in creating the similar composition of advertisement. At this moment, the teacher tried to persuade the students to analyze what features that supported the construction of advertisement. The features of advertisement consists of the name of product, the name of store or company, the quality of product, the address of store or company, the price of product, the contact person, etc. In this case, almost the whole students only paid attention towards teacher’s explanation about the composition of advertisement. To achieve the goal of research, however, the teacher just delivered a brief explanation on how the students should make it properly. Therefore, she preferred to emphasize the students’ speaking ability rather than their writing ability so that the aims of teaching and learning process focused on the speaking skill. After the teacher had explained the way of making composition of advertisement, the teacher let the students to observe the samples of advertisement which were given and pleased the students to ask question when they did not understand. In this stage, the teacher also gave them a time to think about the idea of constructing their advertisement. However, they could not directly solve their problem in completing the assignment. They still needed a help from the teacher in translating the word into English so that the teacher allowed them to search the difficult words in the dictionary. Meanwhile, the teacher helped them to build up their viewpoint to get the inspiration in making the advertisement. In this circumstance, the teacher offered the idea of making advertisement by raising some famous public business place where lots of people commonly visit it frequently and so forth. In the process of constructing the advertisement, the teacher had to describe what type of information that should be written for the content of advertising, namely the name of product, the price, the address of business place, the contact person, the quality, etc. It can effectively aroused their mind to have a plan in creating the idea of their following advertisement. In this section, the teacher stayed to help their students’ problem because it was a very classical matter that concerned to their limited vocabulary. She guided the students to find a suitable vocabulary and give them a time for creating their own creativity to construct an advertisement. In this time, the teacher asked them to make a group so that they can easily share their idea and opinion in order to accomplish the assignment. Since at class there are 38 students so they were divided into six groups. Each of group had for about six to seven members. Each member had own task, such as collecting the picture for their advertisement, composing the content of advertisement, designing the advertisement, and preparing the copies of advertisement for every member. They might help each other to make all the composition done completely. After all of the groups had joined each other, the students began to discuss with their friends about the product or service that they wanted to promote in their project of advertisement. Some students were still confused how to start their work. They admitted that there was no idea about the advertisement at all which they should be made. Then, the teacher explained the examples of advertisements around them. She also mentioned “AW restaurant” for the easiest example for advertisement which exist in the people’s life today. This example was chosen because of the popularity. Their students finally seemed to understand what their teacher’s mean. After getting the point, the students offered another product to their teacher as their future project. Once in choosing a topic for their task, a student claimed to make a shoe shop with their friends as their project of advertisement. Then, the teacher said “It is good idea, you can do it now”. It was a kind of good appreciation to motivate the students’ interest toward the lesson. Some others said that they did not know how to pronounce a word “such as”. Then, the teacher revealed the correct pronunciation for this word /s?t??z./. After the students understood, the teacher reminded them to accomplish their work as soon as possible. However, the students refused to submit it at that time because they were not ready to collect the completed work. Finally, the teacher asked the students to make a good composition of advertisement in written form at home and submitted it in the next meeting. It is used as the media for speaking. The result of project is the students’ speaking. Before ending the class, the teacher emphasized the skill that was going to be scored. The teacher made the students become realized that they had to perform well in speaking ability for the next meeting with their completed project. Hence, they could speak by seeing the advertisement they made. They also must have prepared themselves to be ready in their speaking components which considered to content, fluency, vocabulary, grammar, and pronunciation. The second meeting was conducted on November 20th, 2013. As like the first meeting, the teacher opened the class with greeting and called the name of students one by one to check their presence. As usual, the teacher did not directly teach, but she began the lesson with a simple and short conversation to ask about the students’ condition. Since the way of making an advertisement had been explained in the first meeting, the teacher only asked them to present their project of advertisement that they had been made. The teacher called one group which consists of six to seven members to come forward. They were asked to present their project one by one while the researcher recorded the students’ voice to obtain their transcription as the data of study. In the process of speaking, several students made some errors in spelling, pronunciation, grammar, and diction. In this time, the teacher did corrections on the students’ errors. In the second meeting, there are four examples had collected. Actually, this advertisement is just as the media to facilitate them in producing a spoken advertisement. The four groups must have performed their presentation. Therefore, the result of project is a spoken form project, that is students’ speaking. Based on their presentation, the students frequently made errors in pronunciation and diction. However, they seemed to be braver than before when the speaking section was held. As their errors in pronunciation, they spelled a word “street” with /stre:t/. In fact, the correct one must be /stri:t/. The teacher had did a correction many times towards their mistakes. Then, the students were easily to follow its correct pronunciation. After each member finished presenting their work, the teacher required a representative person to promote the advertisement confidently. In every group’s performance, there will be one of members who were selected to be representative person that must be presented the advertisement in front of the class after all of the members finish performing. By requiring a representative person to represent their group’s presentation, the student got a motivation to be a good speaker. They will consider to perform a nice presentation in front of their friends. From the second observation, it could be concluded that the implementation of Project-Based Learning will help the students’ speaking ability in creating a spoken advertisement. The students also agreed that this model of learning can make them more understand and add more knowledge for them. The third meeting was held on November 27th, 2013. The teacher as usual called the name of students one by one to check the attendance list. Before starting the lesson, teacher did a simple conversation first with their students to make great atmosphere in the class. Then, she tried to remind the assignment that had not been presented yet by some groups. The students with their group started to present their advertisement one by one. Meanwhile, the researcher recorded the students’ speaking to have the students’ transcription. By asking one by one person to come forward, the teacher can evaluate their speaking ability when the presentation is conducted. In conducting the presentation, the students had follows the teacher’s direction and explanation that they must have made the advertisement by adding some information, as like the name of product or service, the quality, kind of items, the contact person, the address, and so forth. As the result, the students who still felt difficult to develop their sentences, they invited another friend to help them. The teacher immediately helped them to compose their speaking with a proper vocabulary. The students showed their project of advertisement and presented the content of advertisement. When the students conducted their presentation, they sometimes made a grammatical and pronunciation errors. The teacher evaluated the students’ speaking by considering some components such as content, pronunciation, grammar, and fluency. In several utterances, they still do not know how to compose the word with a correct structure so that they could not keep the meaning of sentences clearly. For the grammatical errors, the teacher seemed to slightly ignore their mistake and more concentrate into their pronunciation, content, and fluency. Before ending the class, the teacher reviewed a short explanation about the nature of advertisement and its examples around people. The teacher also said about the way to make an advertisement and the important aspect in speaking ability that should be aware by the students, namely fluency, content, vocabulary, pronunciation, and grammar. In the end of class, the teacher did not forget to give appreciation for the students who had performed well in front of class. For the assignment that were still not perfect, the teacher asked the group to accomplish and make it perfect first then they could collect their project to their students. In the last meeting, the researcher gained some information which is in the form of interview towards ten students in the class. The researcher finally obtained the responses of students towards the implementation of Project-Based Learning to the students’ speaking ability. The Analysis of Students’ Ability To resolve the second research question of how the students’ speaking ability, the researcher has conducted the observation towards students’ speaking skill by recording their spoken result. In this research, the researcher intends to examine the result of speaking in two meetings, that are in the second and the third meeting. The assessment included the speaking components which will be elaborated from the students’ spoken advertisement, namely content, fluency, grammar, pronunciation and vocabulary. In the second meeting, some students present the spoken advertisement individually. All members of group 1 come forwards to deliver their presentation. Actually, six or seven members in a group have to present the same spoken advertisement. The teacher evaluated their speaking skill through their presentation. Their spoken advertisement was shown in italic letter below. Student 1 (Group 1): This jacket is very useful for protect us from sunrine, cold weather, all through for stylish. This jacket with the cheap price just eighty thousand rupiahs, many kind of this jacket for example: baseball jacket, parasit jacket, sweater, hodie, and coat. You should have one this jacket, if you don’t have it don’t say you’re an impressive person. From his speaking result, student 1 made some errors in creating his words. He made errors in pronouncing the words. His fluency should also necessarily be considered in speaking assessment. Any grammatical error is still accepted in this text because the construction of a short functional text related to spoken form rather than structural and well-written form. However, in their spoken advertisement are frequently found some errors in diction. They did not know how to place the proper words to another. For example, they used this sentences This jacket is very useful for protect us from sunrine, cold weather, all through for stylish for describing the usefulness of product. For the correct one, they should arrange the choice of words before making a meaningful persuaded utterances. It should be changed by this (This jacket is very useful for protect us from sunrine, cold weather, and stylish model). The word sunrinein their spoken advertisement had to be replaced with (sunrise). Another sample from student 4 in the second meeting has been recorded. The researcher will examine their speaking result based on the component of speaking. Here it is the example from student 4. Student 4 (Group 4): We are group 4, will be presenting about shoes. Casual shoes for boy or girl, trendy shoes highly qualified, colourful, the prices, start of from Rp300.000 till Rp 547.000 size 38-50. If you buy shoes free accessories. Thanks for your attention. According to the speaking result from student 4, she had performed a correct pronunciation in saying English language. She rarely made errors in pronouncing the words. Her fluency is also good because she can speak English fluently without any pause. All those components are considered in speaking assessment. For the correctness in structure or grammar, the errors are still accepted in this text because the construction of a short functional text related to spoken form rather than structural and well-written form. However, in her spoken advertisement, she prefers using simple words than sentences with correct grammar. For example, Casual shoes for boy or girl, trendy shoes highly qualified, colourful, the prices, start of from Rp300.000 till Rp 547.000 size 38-50 to tell the description of product. As like the correct structure, it should be changed by this (Casual shoes for boy or girl, it is trendy shoes with highly qualified, colourful, its prices start from Rp300.000 till Rp 547.000 and the size 38-50.). The word of in their spoken advertisement had to be omitted from the words. In the third meeting, the rest of students come forwards to present their spoken advertisement. Meanwhile, the teacher decided the quality of their speaking skill through their presentation. The researcher has recorded another spoken advertisement was shown in italic letter as follow. Student 2 (Group 2): Permission. We want to offer school supplies such as a beach book and school supplies. If you wish to buy 2 packs get 1 slap book. We opened this program to advance our effort. If you wish to buy the items we sell please go shop for SumberIlmu addressed in the long Manukan No.1. She speaks quite slow and takes some pauses in every single speaking. However, the content is still understandable. She adds polite utterance in her beginning of presentation by saying Permission. According to her spoken advertisement’s transcription, her vocabulary contains variety of words. It had reached good range for the level of Junior High students. Based on the table above, student 2 had made some errors in pronouncing the words. Another correction for her grammatical structure is needed. She did not concern to the use of tense in producing the words, for example, If you wish to buy the items we sell please go shop for SumberIlmu addressed in the long Manukan No.1. Actually, it should be spoken as follows If you wish to buy the items, please go shopping to SumberIlmu addressed in the long Manukan No.1. Student 2 should omit some words like we sell to make the sentences sounds grammatically. The Students’ Responses towards the Implementation of Project-Based Learning Interview is as the instrument for the researcher for gaining the students’ responses towards the implementation of Project-Based Learning. The researcher asked the students in the end of classroom activity. The interview consists of 7 questions in which the students had to answer based on their own opinion and feeling (see appendix). From the students’ response, the researcher will be analyzed the data. Based on the first and second question of interview (1.What do you think about speaking activity in the class? 2. How do you think about this kind of learning method?), the students had delivered their thought about speaking activity in the class. Most of them agreed that speaking activity in the class is a good way for them to train their speaking and learning English. They are motivated to speak in English language because they are accustomed to communicate with English. Another student also felt that studying English through speaking activity is a kind of motivation for them to be active speaker and learner. They admitted that they began to understand about the manner in speaking English. They found that speaking activity can facilitate the problem that is being taught as both the teacher and the students experienced to communicate each other. The observer asked the third question that is (3. What do you think about the method that applied by the teacher? Does it motivate you to learn English?). When the students are persuaded to delivered their opinion about the learning method that is applied, they commented that the method which had implemented make them easy to understand the lesson. They declared that this method also make the lesson become more interesting and clear. It is a good way for the students to study English. In addition, they also said by doing presentation, they could easily understand the English lesson. Therefore, they agreed that this kind of method is excellent way to increase students’ motivation and spirit of study. All of students who are asked to be the respondents totally agreed that they are motivated with the technique that applied by the teacher. Moreover, they are interested to perform the presentation and make an advertisement to deepen their English language. This is the fourth question of interview, What difficulties have you found in speaking class?In identifying the students’ difficulty in speaking English, the researcher had make a question and wanted to know about their opinion. Mostly, the students felt difficulties in composing the sentences because of the limited vocabulary they had. In order to solve this problem, they choose to depend on the tools, such as the dictionary and alfalink. Several students confessed that they have trouble to speak in interpreting and translating some words. Therefore, they are necessarily to open dictionary and use alfalink. The fifth question of the interview is What is the most interesting section in learning English with Project Based learning?The students’ answer about the most interesting part in speaking section for the students was so various. They responded that they prefer to make a sentences into English for presentation and speaking English is their favorite parts of speaking section. Other students also agreed that they like to present in English language and promote the advertisement with this language. Actually, they favored to make advertisement and speak English through it. Based on the last two question are What is the positive impact that you feel from the implementation of Project-Based learning? and Do you think that PBL help you to speak up in the class? Do you like the way of teaching technique? The researcher also asked their statement about the positive impact they got after the implementation of method. They expressed that they were motivated to speak and study English. Some students also uttered that they can increase their knowledge of English language and wanted to continue learning English. Additionally, they felt easily to translate the words while speaking with English. Besides, mostly the students argued that it enable them to speak English correctly. CONCLUSION AND SUGGESTION Conclusion According to the result of research, it is determined that the implementation of Project-Based Learning is applicable method in the language learning process. It has been proved that the students feel interest and enthusiastic in learning English when the method is applied in the classroom. The teacher have conducted the steps of Project-Based Learning so that the students easily follow the instructions and enable them to explore their creativity in creating the project. The students also admit that speaking activity become more attractive and interesting after the implementation of Project-Based Learning. In case of student ability, Project-Based Learning has been encouraged the students’ interest of learning so that they can achieve a good presentation in public speaking because of the Project-Based Learning Method Implementation. As the result, it have been increased their motivation and confidence to speak English in front of the classroom without any boredom and fear. Most of them have a positive response towards this method. Moreover, it have provided an opportunity for the students become active learner and have better understanding of the material, that is short functional text, especially advertisement. Then, the result of speaking ability has been reported as well by describing the students’ speaking ability, related to their speaking components, including content, fluency, vocabulary, pronunciation, and grammar. Finally, it can be concluded that Project-Based Learning is applicable if this method implemented in teaching a spoken advertisement to the eighth graders of Junior High School. This finding is examined based on the instruments of study that have been used, that are field note, observation sheet, interview, and transcription of students’ spoken advertisement. Suggestions In the end of this chapter, there will be several suggestions for the teacher and the researcher. To obtain the advantages of the study, the teacher should consider some important things related to this research. Firstly, because the nature of Project-Based Learning requires a long time for completing the project, the teacher should manage the speaking session as well so that it will not disrupt other materials that are being taught. Actually, the process of making the project should be supervised by the teacher in the class, but in the real learning process, the students create their project at home. In this case, the theory of project-based learning still did not applied entirely. Thus, the researcher may conduct the following research towards this method in order to the phases of method can be completely implemented. Secondly, the students are allowed to choose their own topic of project since it is related to the principle of Project-Based Learning that mainly concerns to students interest of learning. Thirdly, the teacher may ask the students tell their progress of completing the project, it is done in order to the teacher can correct their error and reduce their mistakes of project. Therefore, the teacher can monitor their improvement continuously. In line with the conclusion, Project-Based Learning is applicable implemented in teaching a spoken advertisement to the eighth graders of Junior High School. This method is possibly appropriate to teach another language skill in teaching and learning English language for the lower or higher level of grade. Thus, the further research is suggested to investigate the estimation. REFERENCES Ary, Donald et al. 2010.Introduction to Research in Education. Belmont: Wadsworth Cengage Learning. Brown, H. Douglas. 2000. Teaching by Principles: An Interactive Approach to Language Pedagogy (The Second Edition). New York:Longman. ______. 2006. Standar Isi danStandarKompetensiLulusan: Mata PelajaranBahasaInggris. Jakarta: DepartemenPendidikanNasional. Capraro, Robert M. and Slough, Scott W. 2009.Project-Based Learning An Integrated Science, Technology, Engineering, and Mathematics (STEM) Approach. Rotterdam: Sense Publisher. Cohen et al. 2007. Research Methods in Education (Sixth Edition). New York: Routledge (Taylor & Francis e-library). Davidson, Christina. 2009. Transcription: Imperatives for Qualitative Research. International Journal of Qualitative Methods.8 (2). Estiningrum, DhiahAyu. 2013. The Use of Project-Based Task to Improve Eleventh Graders’ Ability in Writing Hortatory Exposition Text at SMAN 1 NgadirejoPacitan. Unpublished skripsi.UniversitasNegeri Surabaya. Green, Judith L. 2006. Handbook of Complementary Methods in Education Research. London: Lawrence Erlbaum Associates. Harmer, Jeremy. 2001. The Practice of English Language Teaching. London: Longman. Hopkins, Claude C. 2003. Scientific Advertising. Sedona: Carl Galleti. Jones, Leo. 2007. The Students-Centered Classroom. New York: Cambridge University Press. Larmer, John. andMergendoller, John R. 2010. 8 essentials for Project-Based Learning.Educational Leadership.68 (1). Mack, Natasha et al. 2005. Qualitative Methods: A Data Collector’s Field Guide. North Carolina: Family Health International. Mcgonigal, Kelly. 2005. Teaching for Transformation: From Learning Theory to Teaching Strategies. Spring.14 (2). Mergendoller, John R. and Thomas, John W. ______ Managing Project-Based Learning: Principles from the Field. ____________. Nunan, David. 1989. Designing Tasks for The Communicative Classroom. Cambridge: Cambridge University Press. Patton, Allec. 2012. Work that Matters: The Teacher’s Guide to Project-Based Learning. London: Paul Hamlyn Foundation. Prasetyarini, Aryani et al. 2013. English Language Teaching and Learning: Theory and Practice. Yogyakarta: UniversitasSanata Dharma Richards, Jack C and Rodgers, Theodore S. 1986.Approaches and Methods in Language Teaching. Cambridge: Cambridge University Press. Welukar, Rajan, Dr. and Harichandan, Dhaneswar, Dr. 2011. Advertising. Mumbai: University of Mumbai. http://ejournal.unesa.ac.id/index.php/retain/article/view/6225